Tectono‐sedimentary evolution of the Plio‐Pleistocene Corinth rift, Greece. (7th September 2017) - Gawthorpe, Robert L.; Leeder, Mike R.; Kranis, Haralambos; Skourtsos, Emmanuel; Andrews, Julian E.; Henstra, Gijs A.; Mack, Greg H.; Muravchik, Martin; Turner, Jenni A.; Stamatakis, Michael
Abstract: The onshore central Corinth rift contains a syn‐rift succession >3 km thick deposited in 5–15 km‐wide tilt blocks, all now inactive, uplifted and deeply incised. This part of the rift records upward deepening from fluviatile to lake‐margin conditions and finally to sub‐lacustrine turbidite channel and lobe complexes, and deep‐water lacustrine conditions (Lake Corinth) were established over most of the rift by 3.6 Ma. This succession represents the first of two phases of rift development – Rift 1 from 5.0–3.6 to 2.2–1.8 Ma and Rift 2 from 2.2–1.8 Ma to present. Rift 1 developed as a 30 km‐wide zone of distributed normal faulting. The lake was fed by four major N‐ to NE‐flowing antecedent drainages along the southern rift flank. These sourced an axial fluvial system, Gilbert fan deltas and deep lacustrine turbidite channel and lobe complexes. The onset of Rift 2 and abandonment of Rift 1 involved a 30 km northward shift in the locus of rifting. In the west, giant Gilbert deltas built into a deepening lake depocentre in the hanging wall of the newly developing southern border fault system. Footwall and regional uplift progressively destroyed Lake Corinth in the central and eastern parts of the rift, producing a staircase of deltaic and, following drainage reversal, shallow marine terraces descending from >1000 m to present‐day sea level. The growth, linkage and death of normal faults during the two phases of rifting are interpreted to reflect self‐organization and strain localization along co‐linear border faults. In the west, interaction with the Patras rift occurred along the major Patras dextral strike‐slip fault. This led to enhanced migration of fault activity, uplift and incision of some early Rift 2 fan deltas, and opening of the Rion Straits at ca . 400–600 ka. The landscape and stratigraphic evolution of the rift was strongly influenced by regional palaeotopographic variations and local antecedent drainage, both inherited from the Hellenide fold and thrust belt.